The effect of three urease inhibitors on H. pylori viability, urease activity and urease gene expression - Shaalan, Hanaa; Azrad, Maya; Peretz, Avi (Frontiers in Microbiology, 2024)
BackgroundTreatment of Helicobacter pylori (H. pylori) infections is challenged by antibiotic resistance. The urease enzyme contributes to H. pylori colonization in the gastric acidic environment by producing a neutral microenvironment. We hypothesized that urease inhibition could affect H. pylori viability. This work aimed to assess the effects of acetohydroxamic acid (AHA), ebselen and baicalin on urease activity, bacterial viability and urease genes expression in H. pylori isolates.MethodsForty-nine H. pylori clinical isolates were collected. Urease activity was assessed using the phenol red method. The urease inhibition assay assessed inhibitors' effects on urease activity. Flow cytometry assessed the effect of inhibitors on bacterial viability. Real time PCR was used to compare urease genes expression levels following urease inhibition.ResultsUrease activity levels differed between isolates. Acetohydroxamic acid inhibited urease activity at a concentration of 2.5 mM. Although baicalin inhibited urease activity at lower concentrations, major effects were seen at 8 mM. Ebselen's major inhibition was demonstrated at 0.06 mM. Baicalin (8 mM) significantly reduced ATP production compared to untreated isolates. Baicalin, ebselen and acetohydroxamic acid significantly reduced H. pylori viability. Increased urease genes expression was detected after exposure to all urease inhibitors.DiscussionIn conclusion, higher concentrations of baicalin were needed to inhibit urease activity, compared to acetohydroxamic acid and ebselen. Baicalin, ebselen and acetohydroxamic acid reduced H. pylori viability. Therefore, these inhibitors should be further investigated as alternative treatments for H. pylori infection.